2020
DOI: 10.2478/bog-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Using Municipal Tourism Assets for Leveraging Local Economic Development in South Africa

Abstract: AbstractTourism development can be a vital component of place-based development initiatives in the global South. The nexus of tourism and place-based development thinking in the global South and of the role of local governments is only beginning to be investigated by tourism scholars. This article explores the record of using tourism assets in one South African local municipality for leveraging local economic development. Evidence is drawn from the experience of the King Sabata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
6
0
2
Order By: Relevance
“…Caravan parks are part of the basket of immovable assets that South African local municipalities can deploy for boosting tourism and local economic development. Despite the development of a national framework for the management of immovable assets the available evidence shows most government assets in South Africa are underperforming and, in many instances, are in a state of deterioration and/or in need of upgrading (Buys and Mavusa, 2007;Rogerson, 2020). In common with several countries, such as Australia, New Zealand and the United Kingdom, local governments were historically important actors in the development of the caravan park sector in South Africa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caravan parks are part of the basket of immovable assets that South African local municipalities can deploy for boosting tourism and local economic development. Despite the development of a national framework for the management of immovable assets the available evidence shows most government assets in South Africa are underperforming and, in many instances, are in a state of deterioration and/or in need of upgrading (Buys and Mavusa, 2007;Rogerson, 2020). In common with several countries, such as Australia, New Zealand and the United Kingdom, local governments were historically important actors in the development of the caravan park sector in South Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the imperative for appropriate management of assets linked to tourism the limited available research suggests that the recent record of municipalities in South Africa is unimpressive with regards to impacts on local development (Rogerson, 2020;Rogerson and Rogerson, 2020a). In East London, the heart of Buffalo City one of South Africa's eight metropolitan areas, it was concluded that the municipality was "not fully capitalizing on immovable municipal assets to develop, grow and promote tourism" (Dlomo and Tseane-Gumbi, 2017: 1).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurs in Cape Town are typically part of the post-1994 movement for the emergence of a new economy of township tourism that opened up local business opportunities for residents to offer B&B accommodation (Booyens, 2021; C. M. Rogerson, 2004). By contrast, small and microaccommodation providers in the coastal Overstrand are part of a long-established tourism resort that in the post-2000 period shifted from a domestic to an international tourism market anchored on the locality's varied attractions of natural scenery, whale watching, and gastronomy (C. M. Rogerson & Rogerson, 2020b. According to data for 2018 contribution of researcher administered by means of a semistructured questionnaire between June and July 2020 when the country was in stage two of national lockdown.…”
Section: Methodology and Study Areasmentioning
confidence: 99%
“…There are several research knowledge gaps in previous studies, including any about the value of forest resources such as fuel, woods, fruits and nuts, and none prioritized tourism as the dictator or the synergy required of such initiatives to create livelihoods improvement. Rogerson and Rogerson (2019) attested that the essential focus amongst numerous studies clearly revolved around tourism development and local economic development (LED) planning while Rogerson (2020) argued for emphasizing municipality assets as part of place-based economic development initiatives. Henceforth, Rogerson and Rogerson (2020) stated the significance of the inclusive tourism concept and maintained its positivity in empowering previously disadvantaged and marginalized rural communities in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Rogerson and Rogerson (2019) attested that the essential focus amongst numerous studies clearly revolved around tourism development and local economic development (LED) planning while Rogerson (2020) argued for emphasizing municipality assets as part of place-based economic development initiatives. Henceforth, Rogerson and Rogerson (2020) stated the significance of the inclusive tourism concept and maintained its positivity in empowering previously disadvantaged and marginalized rural communities in South Africa.…”
Section: Introductionmentioning
confidence: 99%